Compliance of Business Actors Related to Legalization of Company Regulations in Gresik Regency - Muhammad Shihabuddin Firdaus; Muh. Ali Masnun; Mohammad Setyo Puji Raharjo (NOVUM : JURNAL HUKUM, 2025)
In Article 108 paragraph (1) of Law no. 13 of 2003 concerning Manpower states that entrepreneurs who employ at least 10 (ten) workers/laborers are obliged to make company regulations which come into effect after being ratified by the Minister or appointed official. Referring to this article, business actors in Gresik Regency who have at least 10 (ten) workers/laborers are required to make and record company regulations with the Gresik Regency Manpower Office. In several companies, especially in Gresik Regency, there are still many companies that have not registered or ratified company regulations owned by the Gresik Regency Manpower Office. This is because business actors do not hesitate and comply with the applicable provisions in the Employment Law. This research uses empirical legal research methods with a qualitative approach to obtain primary data obtained and collected directly in the field by direct interviews with informants, namely industrial relations mediators and business actors. The research results show that: First, legal compliance among business actors is still at its lowest point, namely at the level of compliance where someone will comply with a rule because they are afraid of being sanctioned. Second, the efforts made by the Gresik Regency Manpower Office in complying with the law for business actors are preventive, where the Gresik Manpower Service carries out outreach to several companies with direct visits to companies in the Gresik area.